Unexpected haemorrhage from lateral thoracic artery following the removal of a pleural drainage tube. Issue 12 (23rd November 2021) - Matsuura, Keigo; Tada, Makoto; Sumi, Toshiyuki; Osuda, Koichi; Nakata, Hisashi; Chiba, Hirofumi
Abstract: Pulmonologists must be aware of the possible arterial bleeding even during the removal of a safely inserted drain. Abstract : We report an unexpected haemorrhage from lateral thoracic artery following the removal of a pleural drainage tube which had been safely inserted. Pulmonologists must be aware of the possible arterial bleeding even during the removal of a safely inserted drain.